Studies of epoxy powder coated galvanized steel substrate via electrostatic powder coating system - Ajer, Mohd Razali (2012)
This research deals with epoxy powder coating on the electrolytic galvanized steel sheet via electrostatic powder coating system. Normally, the film thickness and powder coverage of the coated powder is not optimum. It leads to non- protection of the parts from rusty and corrosion besides having many defects such as orange peel, rough surface, poor adhesion and inconsistencies of colour tone. In order to produce good coating quality, the processing parameters must be optimized. In this research, there have three variable parameters need to investigate. The variable parameters are total air volume, powder output and spraying distances. These parameters were screening to determine the significant effects to the coating quality. The screening result shows the spraying distance does not have significant effects and it was discarded. The experiments were carrying out to determine the optimum combination of powder output and total air volume. It is purposely to produce sample with good coating quality besides improved the first pass transfer efficiency (FPTE). All samples were tested using same processes that are pre-treatment, dry-off, powder spraying and curing. The method used to investigate the coating characteristic are thickness measurement, Buchholz indentation test, cross cut test, colour visual checking, particle cross-linking struture and surface profile analysis. The instruments used to evaluate the samples are coating thickness gauge, Buchholz indentor, multi blade cutting tools, spectrophotometer, scanning electron microscope (SEM) and surface profiler. The experimental result shows the combination of 4.0 m³/h of total air volume and 150 g/min of powder output produce good coated sample with optimum thickness and colour tone. It also has good particle crosslinking structure and surface profiler. The coating indentation resistant and adhesion for this sampe is able to protect the galvanized steel from corrosion and rusty.